KUALITAS PELAYANAN, HARGA DAN FASILITAS RUMAH KOS DI DESA PLOSOKANDANG DALAM MEMBERIKAN KEPUASAN KEPADA PENGHUNINYA - susilowati, lantip (UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Motivation of this research is the increasing number of boarding houses spread in Plosokandang Village with quality service and competitive prices. The purpose of this research are to find out the quality of service, price and facilities significantly influence the satisfaction of boarding residents in Plosokandang Village. This research uses a quantitative approach to the type of associative research then analyzed using multiple linear regression test. The results of the study show that Quality of service, price and facilities together provide a significant positive effect on the satisfaction of boarding houses in Plosokandang Village.